Encadrer le religieux : une politique de gentrification ? Le cas de l’Institut des Cultures d’Islam de Paris - Víctor Albert-Blanco (Métropoles)
This article analyses the intersection of religious governance and gentrification policies. It focuses on the case of the Institute of Islamic Cultures, designed by the Paris city-council in the 2000s in the heart of the Goutte d´Or neighborhood. While this cultural / religious space can be read as a new variation of religious diversity management (of Islam in particular) implemented by French local authorities, it is also an instrument in line with the urban renewal of the district, as promoted by the public authorities. Through this concrete case, the article shows the importance of the dialectical relationship between religious and the urban spaces, which has so far been little addressed in the literature on gentrification and its policies.